Economic Effects of Fixed-Dose Versus Loose-Dose Combination Therapy for Type 2 Diabetes Patients - Anna-Katharina Böhm; Udo Schneider; Tom Stargardt (Applied Health Economics and Health Policy, 2022)
Objective: We examined the effects of fixe-dose combinations (FDCs) versus loose-dose combinations (LDCs) on costs from the payer and patient perspective and investigated potential channels contributing to differences in costs between the two modes of treatment. Methods We investigated administrative data from 2017 to 2020 on diabetes patients in Germany. After using prospensity-score matching to remove dissimilarities between FDC and LDC patients, we compared changes in costs with a difference-in-differences approach. We analyzed pharmaceutical costs, inpatient and outpatient costs, other costs and total healthcare costs from the payer perspective, and co-payments from the patient perspective. Results The sample comprised 1117 FDC and 1272 LDC patients. Regression analysis revealed that FDC therapy significantly increased antidiabetic pharmaceutical spending in the first year by 5.5% ( p ~<~0.01), but decreased co-payments by 33% ( p ~<~0.01) in the first and 44% ( p ~<~0.01) in the second year. We also observed a trend towards higher outpatient spending in the first year. No significant differences were found with respect to inpatient or other costs. The increase in antidiabetic pharmaceutical spending did not contribute to a significant increase in total healthcare expenditure. We identified a shift of co-payments to the payer and higher adherence as possible mechanisms behind the increase in antidiabetic pharmaceutical spending. Conclusion Although FDC therapy increased disease-specific pharmaceutical spending in the short term, this increase did not lead to differences in total healthcare costs from the payer perspective. From the patient perspective, FDC therapy may be the preferred treatment approach, because of significant saving in co-payments, which is likely attributable to the elimination of one co-payment and therefore a shift in costs to the payer.
Keywords: 610; Pharmacoeconomics and Health Outcomes; Quality of Life Research; Health Economics; Health Administration; Public Health